(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
This paper aims to analyse the accounting and fiscal regime of crowdfunding and the legal framework for such operations in Romania. Crowdfunding provides support to project developers by enabling them to access finance in a simple and inexpensive manner. Thus we refer to the following: current state of crowdfunding operations and existing legal background for conducting such operations in Romania as well as possible directions for its improvement. We will also highlight the accounting and fiscal issues encountered by both companies that hold online crowdfunding platforms and those benefiting from the sums collected through this financing method. This paper is based on case study research method. Considering the fact that in Romania the functioning of the crowdfunding platforms is not yet regulated, the information and views set out in this article are those of the authors.